Diaspora: Dislocation, Development and Drawback - Khanal, Baburam (Interdisciplinary Journal of Management and Social Sciences, 2020)
This study focuses on painful feelings and bitter experiences of diasporas while they are living in the host land. It stresses on their efforts to maintain connections with people in their homeland. Besides, the research talks about diasporas' attempt to assimilate, acculturate and integrate in the host countries in their dislocated and un-homely state. The study also explores the changing attitude of intellectuals, writers, journalists and politicians of host countries towards diasporas, that they have recognized diasporas' positive culture and economic contribution to host societies. Gradually and cautiously host societies and their governments accept diaspora members' affiliations as legitimate and sought for their permanence. Moreover, in some host countries, and in liberal circles, membership of such entities has been regarded as exciting and advantageous but not as an obstacle. Yet, the migrants constantly face criticisms and detriments. They establish networks back in their country of origin and try to influence homeland's politics and sometimes support the violent activities. On top of that, the continued migration and increase in remittances encourage chain of migration and brain drain, and create instability in homeland economy.